Amniotic fluid prostaglandin E2 in pregnancies complicated by preterm prelabor rupture of the membranes. (16th September 2016) - Musilova, Ivana; Andrys, Ctirad; Drahosova, Marcela; Hornychova, Helena; Jacobsson, Bo; Menon, Ramkumar; Laudanski, Piotr; Stepan, Martin; Bestvina, Tomas; Kacerovsky, Marian
Abstract: Objective : To determine amniotic fluid prostaglandin E2 concentrations in women preterm prelabor rupture of the membranes (PPROM) with respect to microbial invasion of the amniotic cavity (MIAC), intraamniotic inflammation (IAI), microbial-associated IAI, histological chorioamnionitis, and short-term neonatal morbidity. Methods : One hundred forty-five women with singleton pregnancies were included in this study. Amniotic fluid samples were obtained by transabdominal amniocentesis and were assayed for prostaglandin E2 concentrations by ELISA. IAI was defined as amniotic fluid interleukin-6 >745 pg/mL. Microbial-associated IAI was defined as the presence of both MIAC and IAI. Result : No differences in prostaglandin E2 concentrations were found between women with and without MIAC ( p  = 0.27). Women with IAI ( p  = 0.0008) and microbial-associated IAI ( p  = 0.01) had higher prostaglandin E2 concentrations than women without these complications. Women with histological chorioamnionitis had higher prostaglandin E2 concentrations only in crude analysis ( p  = 0.02), but not after adjustment for gestational age at sampling ( p  = 0.10). No associations between amniotic fluid prostaglandin E2 concentrations and the selected conditions of severe neonatal morbidity were found. Conclusions : The intraamniotic inflammatory response either to infectious or to non-infectious stimulus, but not MIAC per se, seems to be a main factor associated with the elevation of the amniotic fluid PGE2 concentrations in women with PPROM.